Increasing Learning Achievement in Memorizing Surah Al-Humazah and At-Takatsur Through the Talaqqi Method in Class IV Students of MIN 1 North Aceh - Mustadamah (MADINA : Journal of Islamic Studies, 2024)
The purpose of this study was to determine the improvement of achievement. teacher and student activities and the response of fourth grade students of MIN 1 North Aceh through the Talaqqi Method on the material of Memorizing surah Al-Lahab and Al-Insyirah. This study is a qualitative study with the type of Classroom Action Research (CAR). This study was carried out in 2 cycles, namely the action cycle I consisting of 10 meetings and the action cycle II. The data collected in this study were in the form of test results which included: final test of each cycle's action, observation results which included the results of observations of teacher and student activities, and the results of data distribution of response questionnaires to students. The data source in this study was 21 fourth grade students of MIN 1 North Aceh. For data analysis, the percentage formula was used. The application of learning using the talaqqi method can improve student learning outcomes, with a percentage figure in cycle I of 71.43% and in cycle II becoming 90.47%. The activities of teachers and students using the talaqqi method are included in the very good category. This can be seen from the results of observations of teacher activities which reached 92.19%, while student activities reached 89.06%. The response of students at MIN 1 North Aceh in implementing the talaqqi method was in the very good category, namely 90% stated that they were happy.